A confession [videorecording (DVD)] - Freeman, Martin, 1971-; Staunton, Imelda, 1956-; Finneran, Siobhan, 1967-; Fulcher, Stephen Detective Superintendent (BBC, 2021)
"When 22 year old Sian O'Callaghan goes missing after a Friday night out with friends, Detective Superintendent Steve Fulcher ... quickly realizes that this is no ordinary missing persons case. A prime suspect is identified but when Fulcher questions him about Sian's whereabouts it sets both men on a journey which will change their lives forever as well as reveal the fate of Sian and another local girl, Becky Godden-Edwards. In this fight to get justice for the mothers, Elaine Pickford ... and Karen Edwards ... Steve discovers that the rights of the victim are not always as valued as the rights of the suspect and that his actions have devastating consequences for his career and family."--